Dynamics of hill agriculture in emergent rural economy of Kangra district, Himachal Pradesh - ., NITU; SINGH, R. B. (Journal of Soil and Water Conservation, 2020)
The existence of human beings depends on the mountains and ecosystem services. Farming systems are facing immense difficulties owing to severe water shortage, changing climate patterns, dying traditional knowledge and increasing animal menace. Mountain ecosystem is adversely affected by the pressing population and resultant poverty. Natural resources are under huge pressure with diminishing land and water resources. The present paper examines the agriculture based livelihood security in changing socio-economic environments in district Kangra, Himachal Pradesh. Resource mapping, indexing, scoring and ranking of agro-ecosystem along with human and social capital have been used. In Kangra, about 45% of the work force is dependent on agriculture and the agricultural labourer accounted for 8% of the total work force. There is sluggish growth of employment opportunities in other sectors primarily in secondary and tertiary sectors to absorb surplus labour force from agricultural sector. The district has the largest number of cultivators i.e. 0.3 million out of 2 million cultivators in the state. The diminishing importance of the agro-ecosystem resources and their role as source of income are not sufficient in the present context of livelihood opportunities. The traditional sources of services have been decreasing in importance because of other sources of diversified income along with tourism in the hill region of Kangra. About 60 per cent of the households depend on the livestock for their additional income as well as other nonfarm sources. Integrated farming system improves the livelihood situation and brings financial stability and security.